Synthesis, antimicrobial and in vitro antitumor activities of a series of 1,2,3-thiadiazole and 1,2,3-selenadiazole derivatives - Mhaidat NM; Al-Smadi M; Al-Momani F; Alzoubi KH; Mansi I; Al-Balas Q (Dove Medical Press, 2015)
Nizar M Mhaidat,1,2 Mousa Al-Smadi,3 Fouad Al-Momani,4 Karem H Alzoubi,1 Iman Mansi,2 Qosay Al-Balas5 1Department of Clinical Pharmacy, Faculty of Pharmacy, Jordan University of Science and Technology, Irbid, 2Faculty of Pharmaceutical Sciences, Hashemite University, Zarqa, 3Department of Applied Chemical Sciences, 4Department of Applied Biological Sciences, Faculty of Science and Arts, 5Department of Medicinal Chemistry and Pharmacognosy, Faculty of Pharmacy, Jordan University of Science and Technology, Irbid, JordanAbstract: Three derivatives of substituted 1,2,3-thia- or 1,2,3-selenadiazole (4a–c) were prepared and characterized by different chemical techniques. These compounds were evaluated for their antimicrobial and antitumor activities. Compounds 4a (propenoxide derivative), 4b (carbaldehyde derivative), and 4c (benzene derivative) were active against the yeast-like fungi Candida albicans. Compound 4a was active against gram-negative Escherichia coli, and compound 4c was active against the gram-positive Staphylococcus aureus. For the antitumor activity, both compounds 4b and 4c were active against all tested tumor cell lines, namely, SW480, HCT116, C32, MV3, HMT3522, and MCF-7. The activity of compound 4c was greater than that of compound 4b and more than that of the reference antitumor 5-flourouracil against the SW480, HCT116, and MCF-7 tumor cell lines. In conclusion, a number of the prepared 1,2,3-thia- or 1,2,3-selenadiazole compounds showed promising antifungal, antibacterial, and in vitro antitumor activities. Further investigations are required to explore the mechanism by which active compound are inducing their cytotoxicity. Keywords: thiadiazole, selenadiazole, cell lines, antimicrobial activity